Landscape establishment and irrigation management of ornamental plants grown in eastern redcedar substrate - Carmichael, Travis Rex (Kansas State University, 2013)
Pine bark (PB) has been the principal component of nursery crop substrates in the United States for more than 60 years. Substrate material used for the purpose of growing ornamental plants in the Great Plains is generally shipped a great distance, primarily from the Southeastern U.S., due to a lack of pine plantations in this region. Eastern redcedar (Juniperus virginiana L.; ERC), an aggressively weedy tree species, has been identified as a possible alternative to PB for nursery substrates. The objective of this thesis was to evaluate the establishment of Miscanthus sinensis N.J. ‘Little Kitten’ (dwarf maiden grass), Rosa (L.) ‘Radtkopink’ (Knockout® rose), Ilex glabra (L.) A. Gray ‘Compacta’ (holly), Ulmus parvifolia Jacq. ‘Emer II’ (Allee® lacebark elm), Sedum telphium L. ‘Autumn Joy’ (sedum), Hosta Tratt. ‘Sum and Substance’ (hosta), and Hemerocallis L. ‘Charles Johnston’ (daylily) in three substrate mixes. These substrate mixes consisted of 80% PB: 20% sand, 80% ERC: 20% sand, and 40% PB: 40% ERC: 20% sand. At the end of the production phase differences in growth were observed in maiden grass, holly, lacebark elm, and sedum. At the end of the landscape establishment phase, no differences in growth were observed in any species except holly and hosta. To attempt to overcome the sub-optimal physical properties of ERC (high air space and low container capacity), cyclic irrigation was used to evaluate growth of Sedum spectabile Boreau ‘Autumn Fire’ (sedum), Rudbeckia fulgida Aiton ‘Goldstrum’ (black-eyed susan), and Hibiscus moscheutos L. ‘Luna White’ (hibiscus) in the same 3 substrates. The objective of this study was to evaluate the affect of irrigation frequency (1x, 2x, 3x, or 6x per day) and substrate ERC content on plant growth. Sedum had the greatest growth index (GI) shoot dry weight in PB and when irrigated 1x and 2x per day had the greatest root dry weight regardless of substrate. Irrigation frequency had no significant difference for GI and shoot dry weight Black-eyed susan had the greatest GI and shoot dry weight when grown in PB. Irrigation frequency only had an impact on shoot dry weight of black-eyed susan; plants irrigated 1x, 2x, and 3x per day had the greatest growth. Hibiscus had greatest growth in PB: ERC mix. Irrigation frequency had no impact on growth of hibiscus. Cyclic irrigation does not overcome low water holding capacities in these three species. Overall, ERC can be used as a partial replacement to PB (up to 50%). However, further research evaluating effects of different fertility regimes on ERC substrate is warranted.
Keywords: Juniperus virginiana; Cyclic irrigation; Amendment; Alternative; Sustainable; Media; Horticulture (0471)